2000
DOI: 10.1542/peds.106.5.977
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Bacteremia in Febrile Children 3 to 36 Months of Age

Abstract: Use of the formulas derived here allows the clinician to estimate a child's risk for bacteremia based on temperature, ANC, and gender. This approach offers a useful alternative to predictions based on fever and WBC alone.bacteremia, detection, white blood cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 22 publications
2
39
2
Order By: Relevance
“…9,[13][14][15][16][17][18][19] Our finding that body temperature is not an accurate marker of serious bacterial infection has been reported previously in a small sample of febrile children (n = 138) within a narrow age range (under 1 year of age). 9 Studies that included temperature in their multivariate analysis of possible predictors of bacteremia or serious bacterial infection have reported odds ratios that suggest a poor test performance of temperature in their multiple regressions models.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…9,[13][14][15][16][17][18][19] Our finding that body temperature is not an accurate marker of serious bacterial infection has been reported previously in a small sample of febrile children (n = 138) within a narrow age range (under 1 year of age). 9 Studies that included temperature in their multivariate analysis of possible predictors of bacteremia or serious bacterial infection have reported odds ratios that suggest a poor test performance of temperature in their multiple regressions models.…”
Section: Discussionsupporting
confidence: 43%
“…9 Studies that included temperature in their multivariate analysis of possible predictors of bacteremia or serious bacterial infection have reported odds ratios that suggest a poor test performance of temperature in their multiple regressions models. 16,18,20 To our knowledge no prior studies have investigated the effect of age, appearance, or duration of illness on the accuracy of temperature as a marker of serious bacterial infection. This is a large prospective cohort study of a wide pediatric age group that has evaluated the diagnostic test performance characteristics of temperature as a marker of serious bacterial infection in the post pneumococcal vaccination era.…”
Section: Discussionmentioning
confidence: 99%
“…The yield from blood culture depends upon the volume of blood taken; 1-5 ml is recommended from infants and children. The yield has been noted to increase by approximately 3% per ml of blood culture [4][5][6].…”
mentioning
confidence: 99%
“…11 Experienced clinicians use a combination of clinical judgment, these guidelines, clinical and laboratory indices, immunization status and demographic risk factors to identify children at increased risk of bacteremia and then base treatment decisions on this empiric risk assessment. 2,12,13 During prelicensure studies at Kaiser Permanente in Northern California, it was shown that the heptavalent conjugated pneumococcal vaccine (PNCV7; Prevnar) was highly effective at preventing invasive pneumococcal disease. Studies after the introduction of routine conjugated pneumococcal immunizations have shown a substantial drop in the incidence of pneumococcal bacteremia in the toddler age group.…”
mentioning
confidence: 99%